Co-Existing Point of Equilibrium in Discretization of Fractional-Order Prey and Predator Model - Rio Satriyantara; Dara Puspita Anggraeni; Irma Risvana Dewi; Alfian Eka Utama (Eigen Mathematics Journal, 2023)
In this work, a discretization process of a fractional-order prey and predator model is discussed. The aim of this work is to describe the population phenomenon which contains prey and predator. In this research, the prey and predator model by Ghosh et al. (2017) is used. The model has an unique form because it contains prey refuge and additional food to predator. In order to give more details on prey and predator population, the model then modified into fractional order and then discretized. The discretization model has three points of equilibrium and one of them named co-existing point of equilibrium. The numerical simulation is used to perform the stability. The numerical simulation is controlled by using mathematical programming language. It resulted that the co-existing point of equilibrium tends to be stable or converge if a small value of  (time step) is selected. Otherwise, if a larger value of  is selected, then oscillatory is appeared which means the point of equilibrium become unstable or diverge.